Resonance properties of the vocal folds: in vivo laryngoscopic investigation of the externally excited laryngeal vibrations - Svec, J G; Horácek, J; Sram, F; Veselý, J (The Journal of the Acoustical Society of America, 2000)
The study presents the first attempt to investigate resonance properties of the living vocal folds by means of laryngoscopy. Laryngeal vibrations were excited via a shaker placed on the neck of a male subject and observed by means of videostroboscopy and videokymography (VKG). When the vocal folds were tuned to the phonation frequency of 110 Hz and sinusoidal vibration with sweeping frequency (in the range 50-400 Hz) was delivered to the larynx, three clearly pronounced resonance peaks at frequencies around 110, 170, and 240 Hz were identified in the vocal fold tissues. Different modes of vibration of the vocal folds, observed as distinct lateral-medial oscillations with one, two, and three half-wavelengths along the glottal length, respectively, were associated with these resonance frequencies. At the external excitation frequencies below 100 Hz, vibrations of the ventricular folds, aryepiglottic folds and arytenoid cartilages were dominant in the larynx.
Keywords: Electrokymography; laryngoskopie; Vibration; hlasové řasy; zvuková spektrografie; mužské pohlaví; Laryngoscopy; Sound Spectrography; Adult; elektrokymografie; Humans; vibrace; Video Recording; Phonation; fonace; dospělí; Vocal Cords; lidé; Male; audiovizuální záznam